(3GdCZPjI hGdCTQHI ddCUMGAs - (3eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO, GdfLjH GdSeQbfOj , J (B619 (3g` s
(3ChdgG (B:s
(3bGd GdTjN fLjH GdOjf GdSeQbfOi(B:(3Gf Gddg JHGQc hJYGdi Ndb fhY GdGfSGf ,GYO dg eRGLG ef LejY GdMjhGfGJ s
(3BNQgG (B:s
(3hYfO GdVYa hGdZTi , CcKQ hCTO ef ESJYeGdg SGFQ GdQhGFM GdWjHI s
(3bWYI Jchf GdbSe GdQGHYs
(3hJbGHd aj GdfSNI GdeJbOeI ef GdhQbI (B114 (3H Edi (B151 (3Cs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
Keywords: (3GdWHs